2020
DOI: 10.1103/physrevd.102.043019
|View full text |Cite
|
Sign up to set email alerts
|

Axion helioscopes as solar magnetometers

Abstract: Axion helioscopes search for solar axions and axionlike particles via inverse Primakoff conversion in strong laboratory magnets pointed at the Sun. Anticipating the detection of solar axions, we determine the potential for the planned next-generation helioscope, the International Axion Observatory (IAXO), to measure or constrain the solar magnetic field. To do this we consider a previously neglected component of the solar axion flux at sub-keV energies arising from the conversion of longitudinal plasmons. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 115 publications
(177 reference statements)
1
73
0
Order By: Relevance
“…where κ is the Z 2 -preserving coupling between two dark scalars and a Higgs, κ S 2 h, that can be computed in terms of the Lagrangian parameters in (89).…”
Section: A Minimal Dark Scalar Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where κ is the Z 2 -preserving coupling between two dark scalars and a Higgs, κ S 2 h, that can be computed in terms of the Lagrangian parameters in (89).…”
Section: A Minimal Dark Scalar Modelmentioning
confidence: 99%
“…In some cases, this process may even dominate over the Primakoff rate, although there are some uncertainties on the exact structure of the magnetic field in the solar interior. See Refs [88][89][90][91]. for recent analyses.…”
mentioning
confidence: 99%
“…One way to search for axion dark matter is by observing its decay into two photons [13][14][15][16][17][18][19][20][21][22][23][24]. However, compact objects have long been known to offer a useful avenue in which to probe axions and ALPs in a variety of ways [25][26][27][28][29][30][31][32][33]. Neutron stars (NSs) in particular offer an exciting opportunity for increasing the possibility to detect axion dark matter by allowing axions to resonantly convert into radio photons in their magnetospheres.…”
Section: Jhep09(2021)105mentioning
confidence: 99%
“…A more detailed study by Guarini et al [39] found that solar large-scale magnetic fields enhance the axion emissivity by the coherent conversion of thermal photons to axions. It was also reported that, in the Sun, the plasmon-axion conversion could compete with the Primakoff production of axions [58]. Equally, Caputo et al [21] found that, depending on the strength and nature of the solar magnetic field, the plasmon-axion conversion dominates over Primakoff production for energies lower than 200 eV .…”
Section: Introductionmentioning
confidence: 98%